A design and evaluation tool using 3D head templates. Issue 2 (3rd March 2016) - Luximon, Yan; Ball, Roger M.; Chow, Eric H.C.
Abstract: Product fit greatly depends on the human anthropometric information. Traditional anthropometric dimensions do not describe the 3D shape of the human body that is required by product designers, especially for head fitting products. With the development of CAD software and 3D scanning technology, 3D human modeling is becoming more important in design area. Based on SizeChina database, a 3D digital design and evaluation tool that allow designers to easily access Chinese head and face shape data in the Solidworks CAD environment has been developed in this study. The various sizes of 3D head templates are generated in using reference dimensions. This digital design tool can be used to visualize, evaluate and correct product fit on screen during the development process. This method allows the creation of better fitting products for the head and face. GRAPHICAL ABSTRACT: